Algae biorefinery: Review on a broad spectrum of downstream processes and products. (November 2019) - Khoo, Choon Gek; Dasan, Yaleeni Kanna; Lam, Man Kee; Lee, Keat Teong
Highlight: Algae biomass is a feasible feedstock for biofuels and bioproducts synthesis. Algae biorefinery can optimise resources, maximize profits and minimize wastes. Process development on algae-based biofuels and bioproducts were evaluated. LCA is crucial in developing algae biorefinery. Tailored design algae-based-biorefinery requires more intensive research. Abstract: Algae biomass comprises variety of biochemicals components such as carbohydrates, lipids and protein, which make them a feasible feedstock for biofuel production. However, high production cost mainly due to algae cultivation remains the main challenge in commercializing algae biofuels. Hence, extraction of other high value-added bioproducts from algae biomass is necessary to enhance the economic feasibility of algae biofuel production. This paper is aims to deliberate the recent developments of conventional technologies for algae biofuels production, such as biochemical and chemical conversion pathways, and extraction of a variety of bioproducts from algae biomass for various potential applications. Besides, life cycle evaluation studies on microalgae biorefinery are presented, focusing on case studies for various cultivation techniques, culture medium, harvesting, and dewatering techniques along with biofuel and bioenergy production pathways. Overall, the algae biorefinery provides new opportunities for valorisation of algae biomass for multiple products synthesis.